Making Sense of, and Responding Sensibly to, Psychosis. (September 2019) - Read, John
This article argues that words like "psychosis" and "schizophrenia" create the illusion of an explanation for certain behaviors and thoughts but actually explain nothing. Hearing distressing voices and feeling very paranoid do not occur because someone has something called "schizophrenia" that causes them to act in certain ways, although many psychiatrists still cling to this delusion. The behaviors and thoughts that experts in some cultures label psychotic or schizophrenic are usually understandable reactions to our life events and circumstances. So rather than ask, "What is wrong with you?" and "What shall we call it?" It is more sensible, and useful, to ask, "What happened to you?" and "What do you need?"